Neurobeha vioural effects of Inorganic lead exposure in battery workers in Selangor - Suliaman, Muhammad Nasir (2007)
INTRODUCTION: The usage of lead progressively increased with industrialisation and rose dramatically with the widespread use of automobile in the twentieth century. Nowadays, it is predominantly used in the lead-acid batteries with estimated 76% of annual primary and secondary lead usage. Human can be exposed to lead through the general environment and occupations but it is the latter that poses major concern because almost 95% of all adult lead intoxication is of occupational in origin (Shwartz, 2001 ). Among the organs affected by lead are of lead are cardiovascular, renal, reproduction, haematology, gastrointestinal, hepatic and central nervous system. Early effects of lead on the central nervous system can be subclinical and test of neurobehavioural is one method to detect these effects. Although battery manufacturing is the major user of lead, currently, there is very limited data available on the level of lead exposure and its neurobehavioural effects on battery workers in Malaysia. OBJECTIVE: The objective of this study is to assess the neurobehavioural performances of battery manufacturing plant workers. METHODOLOGY: This is a cross sectional comparative study comparmg the neurobehavioural effects of lead among 44 exposed and 33 non-exposed from three battery manufacturing plants and one battery reclamation and recycling plant. Exposure was assessed through personal monitoring of exposure to lead at different sections of the plants; blood lead level was checked as a biomarker and symptoms and neurobahavioural xvii outcome was assessed using standard WHO questionnaire and Neurobehavioural Core Test Battery respectively. RESULTS: Thirteen of twenty points of monitoring showed level above Permissible Exposure Limit (Range <1J.Lg/m3 to 768.88 J.Lg/m3}.The sections (no.) with the level above the Permissible Exposure Limit were grid casting (2), grid pasting (2), quality control (3), assembly lines (2}, battery cutting (1 ), furnace-melt (1 }, battery smelting (1) and housekeeping (1 ). Median blood lead levels for exposed and non-exposed workers were 11.10 and 9.45 J.Lg/dL respectively. Exposed workers were noted to have higher proportion of forgetfulness (29.5%), excessive sweating (13.6%), diarrhea (15.9%), weakness of lower body (25.0%) and change of sense of taste (9.1 %) but none was significant. Sixty three percents of exposed workers wore face mask while working but only 6.8% change their cloth before going home. Only small proportion of exposed workers eat and smoke while working (4.5% and 13.6% respectively). Exposed workers scored lower in Benton Visual Retention, Digit Span, Pursuit Aiming, Digit Symbol, and Santa Ana Manual Dexterity Non-dominant Hand. Only Pursuit Aiming Test was significant (p=O.O 18). There were inverse associations in workers in the higher blood lead level category (~12.2J.Lg/dL) in the tests of Pursuit Aiming, Simple Reaction Time, Profile of Mood States (total score), Tension-Anxiety, Depression-Dejection and Vigour, in reference to workers in the category of lower blood lead level (::S8J.Lg/dL) but these associations were not significant. DISCUSSION: Different sections of different factories have different levels of environmental lead from very low level to a very high level. Despite being exposed to high concentration of lead at certain sections, the blood lead levels of the workers are still below the action level. This is due to due to the protective measures practiced by the workers and compliance to the law by the employer that protects the workers. Neurobehavioural symptoms and performance score were not significant between the exposed and non-exposed which was reflected by the insignificant difference in blood lead level between these two groups. CONCLUSION: The workers in the studied battery manufacturing plants are exposed to lead at varying level depending on the sections in the factory. However, through proper protective measures, safe work practices and employers compliance to the law, the workers were protected from this exposure. There were also no significant inverse association between blood lead levels and neurobehavioural performances in battery manufacturing plant workers.